Heat transfer - Holman, Jack Philip, 1934-2013 (Boston : McGraw Hill Higher Education, 2010)
As one of the most popular heat transfer texts, Jack Holman's Heat Transfer is noted for its clarity, accessible approach, and inclusion of many examples and problem sets. The new tenth edition retains the straight-forward, to-the-point writing style while covering both analytical and empirical approaches to the subject. Throughout the book, emphasis is placed on physical understanding while, at the same time, relying on meaningful experimental data in those situations that do not permit a simple analytical solution. New examples and templates provide students with updated resources for computer-numerical solutions.
Includes bibliographical references and index.
Keywords: Heat -- Transmission